Extração e caracterização de amido de quinoa, cañihua e Mirabilis jalapa - Pumacahua Ramos, Augusto [UNESP] (2014)
The main objective of this research was to extract and characterize starch grain of quinoa (Chenopodium quinoa Willd.), cañihua (Chenopodium pallidicaule Aellen) and marvel (Mirabilis jalapa). The moisture sorption isotherm data of grains and starch of quinoa were investigated at different temperatures and relative umidity and adjusted to mathematical models of GAB, Peleg, Caurie, Ferro-Foltan, Smith and Halsey. The activation energies and isosteric heats of adsorption were determined. It was investigated the phenomenon of mass transfer in quinoa grain hydration at different times and temperatures by Fick's second law model, and the effective diffusivity was calculated. Temperature dependence of the effective diffusivity was described by Arrhenius-type relationship. The extraction of starches from quinoa and cañihua was performed by wet milling and starch marvel by mechanical separation. The starches were characterized according to amylose composition, size and shape of the granules, roughness, relative crystallinity, heat resistance, gelatinization enthalpy, paste properties and others. Instrumental techniques such as scanning electron microscopy, atomic force microscopy, X-ray diffraction, spectroscopy infrared, spectrophotometry, thermogravimetry, differential scanning calorimetry, rapid viscoamylographic analysis, particle size analyzer were used in the characterization of starches. The results confirmed similar studies and other unpublished information were obtained that can be used to make better use of grains and starches